CURRICULUM UNIVERSITARIO GÉNERO SENSITIVO E INCLUSIVO - Bolaños Cubero, Carolina (2023)
The article refers to the need of transforming the unequal relationships between men and women which propitiate gender violence in different dimensions of society, being some of them the ones developed throughout the educational processes, especially at the university level. For that reason, the construction of an inclusive university curriculm, sensible to gender differences, is proposed based on a critical education position in order to generate changes in educational practices and university communality, which will enable the transformation of a patriarchal social organization.